2022
DOI: 10.3389/fimmu.2021.814709
|View full text |Cite
|
Sign up to set email alerts
|

The cGAS-STING Pathway in Bacterial Infection and Bacterial Immunity

Abstract: Cyclic guanosine monophosphate (GMP)-adenosine monophosphate (AMP) (cGAMP) synthase (cGAS), along with the adaptor stimulator of interferon genes (STING), are crucial components of the innate immune system, and their study has become a research hotspot in recent years. Many biochemical and structural studies that have collectively elucidated the mechanism of activation of the cGAS-STING pathway with atomic resolution have provided insights into the roles of the cGAS-STING pathway in innate immunity and clues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 159 publications
0
40
0
Order By: Relevance
“…We corroborate that P. aeruginosa bacteria in keratitis likely possess a high content of c-di-GMP that promotes persistent biofilm pathogenesis and reduced production of cytokines. The efficiency of bacterial clearance by the host could also be affected by activation of the cyclic GMP-AMP synthase stimulator of interferon gene (cGAS-STING) pathway, which has been reported to be involved in protecting the host by activating the innate immune response during bacterial infection ( 48 50 ). Apart from bacterial DNA, cyclic dinucleotides like c-di-GMP and c-di-AMP can also activate cGAS, which in turn triggers STING to initiate the host immune response ( 51 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…We corroborate that P. aeruginosa bacteria in keratitis likely possess a high content of c-di-GMP that promotes persistent biofilm pathogenesis and reduced production of cytokines. The efficiency of bacterial clearance by the host could also be affected by activation of the cyclic GMP-AMP synthase stimulator of interferon gene (cGAS-STING) pathway, which has been reported to be involved in protecting the host by activating the innate immune response during bacterial infection ( 48 50 ). Apart from bacterial DNA, cyclic dinucleotides like c-di-GMP and c-di-AMP can also activate cGAS, which in turn triggers STING to initiate the host immune response ( 51 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…STING is a key receptor protein in the natural immune response pathway ( 31 ). After PRRs recognize cytoplasmic viral nucleic acids, the conformation changes after STING binds to these receptors.…”
Section: Itaconate Negatively Regulates the Sting Pathway To Modulate...mentioning
confidence: 99%
“…The cGAS-STING pathway is a major inducer of IFN-I in response to both exogenous, pathogen-derived DNA, as well as host mitochondrial and nuclear DNA (45,51,52,(93)(94)(95)(96). cGAS non-discriminately binds double stranded DNA and produces cGAMP that binds and activates STING on the ER.…”
Section: B Burgdorferi Elicits Robust Innate and Adaptive Immune Resp...mentioning
confidence: 99%
“…This results in the recruitment and activation of Tank-binding Kinase 1 (TBK1), leading to the phosphorylation of Interferon Regulatory Factor 3 (IRF3) for the induction of type I interferons (IFNα, β) and ISGs (4244). Although initially identified as an antiviral host defense pathway, it is now well known that the cGAS-STING pathway is critical for induction of robust IFN-I responses to intracellular bacteria such as Mycobacterium tuberculosis and Listeria monocytogenes (45, 50, 51). A recent study revealed that the cGAS-STING pathway is also essential for IFN-I production in response to multiple extracellular pathogens, including Pseudomonas aeruginosa, Klebsiella pneumoniae , and Staphylococcus aureus (52, 53).…”
Section: Introductionmentioning
confidence: 99%